Pendampingan dan Pelatihan Penyusunan Laporan Keuangan Praktis dengan Mengaplikasikan Microsoft Excel pada UMKM Omah Jamu Argomulyo - Sebayang, Laura Sindhea; Candra, Yudas Tadius Andi (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2024)
The purpose of this service activity is to help Omah Jamu Argomulyo MSMEs become proficient in using Microsoft Excel to create financial report formats and prepare useful financial reports. The goal of this service is to help MSME owners and managers become more knowledgeable and proficient in creating financial reports, which includes keeping track of everyday activities and creating balance sheets and profit and loss statements. In addition, the course covered how to use Microsoft Excel to generate useful and effective financial report forms for MSMEs. The techniques used include one-on-one training and mentoring sessions that culminate in an activity evaluation, as well as interviews performed prior to service projects. The activity's outcomes demonstrate a notable improvement in MSME owners' capacity to create clear and accurate financial reports. Omah Jamu Argomulyo UMKM is anticipated to improve the effectiveness of financial management through more structured financial reports. The program's success creates chances for additional advancement and application to other MSMEs. Keywords: Training and simulation; Practical money management; Microsoft Excel